Propagación asexual de pitahaya (Hylocereus undatus) mediante estacas empleando enarizadores ANA y AIB en el canton Puerto Quito. - Torres Cordero, Edwin Alfredo (2015)
The present work was performed at the Campus Union Cariamanga Canton " Puerto Quito " Pichincha province whose coordinates , geographic is 01º 13 ' 0 " S and 78 ° 31' 0" West longitude, at an altitude of 200 m, s . n . m ; asexual propagation of pitaya ( Hylocereus undatus ) was assessed by using stakes enraizadores ANA and AIB .In this paper the asexual propagation of pitaya (Hylocereus undatus) was assessed by using Rooting cuttings NAA and IBA in the canton Puerto Quito, using a completely randomized design with five replicates for each treatment. This fruit has been well received nationally and internationally. Today in Ecuador are investigating its use and why it is important to study its propagation, the different hormone levels in root induction in this species, including T1 with 1000 mg kg ˉ ¹ AIB + 1000 mg kg ˉ ¹ ANA, T2 1500 mg kg ˉ ¹ AIB + 1500 mg kg ˉ ¹ ANA, T3 with 2000 mg kg ˉ ¹ AIB + 2000 mg kg ˉ ¹ ANA and a control (no hormone) combined with substrate soil and sand that are the treatments under study. At 45 days, the mortality rate, percentage of rooting, number of roots, greater root length and shoot length, applying the Tukey test to determine significant differences between the measurements of the treatments was evaluated. Overall best response was obtained in T3 concentration 2000 mg kg ˉ ¹ AIB + 2000 mg kg ˉ ¹ ANA was the best number of roots 10.40; Root length 20.8 cm; rooting percentage of 96.20% and mortality rate of 3.80%, exceeding the control and other treatments, and with 22% return.; therefore it can spread vegetatively.